Risk Communication and Community Engagement (RCCE) implementations to control cholera outbreak in Oromia region, Ethiopia - Dabesa Gobena; Esayas Kebede Gudina; Getahun Fetensa; Tizta Tilahun Degfie; Tessema Debela; Afework Tamiru; Zenebu Begna Bayissa; Dereje Diriba; Tarekegn Sarbessa; Daniel Bekele; Natinel Teferi; Achalu Layesa; et al. (Tropical Medicine and Health)
Abstract Background Oromia regional state experiencing cholera outbreaks in a protracted pattern despite various interventions at local and regional levels. This study aimed to examine the implementation of Risk Communication and Community Engagement (RCCE) activities for cholera outbreak control in the region. Methods We conducted a quantitative and qualitative mixed-method study. The study included 422 respondents for quantitative, 22 key informant interviews (KII), and 4 Focus Group Discussions (FGDs) for the qualitative methods. Risk Communication and Community Engagement (RCCE) activities were assessed using standard questionnaires adapted from national cholera guideline later categorized as poor, satisfactory and good. The findings have also been derived qualitatively from three distinct themes or pillars, specifically (coordination and logistics, RCCE, and the Oral Cholera Vaccine). The quantitative data were analyzed using Stata, version 14.0, and ATLAS.ti9 software was used for qualitative data analysis. An ordinal logistic regression model was applied to identify factors associated with the RCCE status, and a thematic content analysis was performed for the qualitative study. Odds Ratios with 95% confidence intervals (CI) were used to present the findings from the quantitative analysis. Results Only 53% (223) of participants had received health information on cholera of whom 22.8% (96) had material for Social Behaviour Change (SBC) in the local language (Afan Oromo). The overall RCCE implementation status was rated as poor by 73% of the respondents, satisfactory by 23%, and only 4% rated it as good. Level of education and occupation of the house are among the factors affecting the implementation of RCCE. The qualitative findings revealed a lack of regular community dialogues, and community engagements were notably minimal during the early phase of the outbreak. Overall, the RCCE implementation activities were characterized by inconsistency, a lack of comprehensiveness, and uniformity across all levels. Conclusion The RCCE-related intervention activities were found to be minimal, inconsistent and less focused. The RCCE interventions and awareness creation need to begin with the small units of the community structures, including individuals and families and have to happen continuously with the community, and health workers' involvement at all level. Preliminary evaluation of Social and Behaviour Change (SBC) materials before their distribution should be made, and adopting diverse communication modalities to control the outbreak.